Inquiry, Logic, and International Politics : With a New Preface by Harvey Starr - Most, Benjamin A., -1986; Starr, Harvey (Studies in international relations (Columbia, S.C.), 2015)
Through the use of logic, simulation, and empirical data, Benjamin A. Most and Harvey Starr develop and demonstrate a nuanced and more appropriate conceptualization of explanation in international relations and foreign policy in Inquiry, Logic, and International Politics. They demonstrate that a concern with the logical underpinnings of research raises a series of theoretical, conceptual, and epistemological issues that must be addressed if theory and research design are to meet the challenges of cumulation in the study of international relations (or any area of social science). The authors argue for understanding the critical, yet subtle, interplay of the elements with a research triad composed of theory, logic, and method.